PENGARUH KOMPENSASI NON FINANSIAL TERHADAP EFEKTIFITAS KINERJA PEGAWAI (Studi Pada Pegawai BKPP Kabupaten Sumbawa) - Marisa Sutanty; Wila Dianti; K Kamaruddin (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
The purpose of this study was to determine the effect of non-financial compensation variables on the Work Effectiveness of Employees at the Staffing, Education and Training Agency of Sumbawa Regency. This type of research is explanatory research. The population in this study are all employees at the Staffing, Education and Training Agency of Sumbawa Regency, totaling 52 people and the entire population will be used as a research sample or population research or census research. Data was collected through questionnaires or questionnaires distributed to research respondents. Data analysis was carried out using simple linear regression analysis techniques, partial hypothesis testing (t test), and determination coefficient test (R2). The results showed that non-financial compensation had a positive and significant effect on the effectiveness of employee performance at the Staffing, Education and Training Agency of Sumbawa Regency. the degree of influence of non-financial compensation on the effectiveness of employee performance at the Staffing, Education and Training Agency of Sumbawa Regency is 44%, while the remaining 56% is influenced by other variables outside the scope of this study.